Governance and transnational civil society: the problem of transnational rent-seeking - Gerard Clarke (Journal of Civil Society, 2016)
The expansion of transnational civil society challenges the regulatory reach of nation-states, both individually and collectively. One regulatory challenge is that transnational civil society organizations (TCSOs) can avail of opportunities to engage in, or facilitate, transnational rent-seeking in ways which benefit a small group of organizations or individuals but which impose significant social costs. This article suggests that certain roles played by TCSOs lend themselves to rent-seeking behaviour and it explores the hypothesis that transnational civil society organizations can engage in, or facilitate, transnational rent-seeking where they constitute transnational special interests and/or private transnational authorities. To this end, the article outlines a brief theoretical framework and applies it to case studies of two TCSOs, representing transnational trade associations and industry lobbies, and sports associations and regulators. While the conclusions here are tentative, the article argues for further research including refinement of the theoretical framework and empirical testing.